Neural Plasticity in Spinal and Corticospinal Pathways Induced by Balance Training in Neurologically Intact Adults: A Systematic Review - Sun, Yao; Hurd, Caitlin L.; Barnes, Michelle M.; Yang, Jaynie F. (Frontiers in Human Neuroscience, 2022)
Balance training, defined here as training of postural equilibrium, improves postural control and reduces the rate of falls especially in older adults. This systematic review aimed to determine the neuroplasticity induced by such training in younger (18 -30 years old) and older adults (≥ 65 years old) . We focused on spinal and corticospinal pathways, as studied with electrophysiology, in people without neurological or other systematic disorders. We were specifically interested in the change in the excitability of these pathways before and after training. Searches were conducted in four databases: MEDLINE, CINAHL, Scopus, and Embase. A total of 1172 abstracts were screened, and 14 articles were included. Quality of the studies was evaluated with the Downs and Black checklist. Twelve of the studies measured spinal reflexes, with ten measuring the soleus H-reflex. The H-reflex amplitude was consistently reduced in younger adults after balance training, while mixed results were found in older adults, with many showing an increase in the H-reflex after training. The differences in results between studies of younger versus older adults may be related to the differences in their H-reflexes at baseline, with older adults showing much smaller H-reflexes than younger adults. Five studies measured corticospinal and intracortical excitability using transcranial magnetic stimulation. Younger adults showed reduced corticospinal excitability and enhanced intracortical inhibition after balance training. Two studies on older adults reported mixed results after training. No conclusions could be drawn for corticospinal and intracortical plasticity given the small number of studies. Overall, balance training induced measurable change in spinal excitability, with different changes seen in younger compared to older adults.